تحكم الي

Download as pdf or txt
Download as pdf or txt
You are on page 1of 6

LAPLACE TRANSFORMATION.

Laplace transform of f(t) is given by

 f (t ).e
 ST
[ f ( t )]  F ( s )  dt
0

Inverse Laplace transformation

c  j
1
 F ( s ).e
1
 [ F ( s )]  f (t )  ST
ds for t > 0
2 j c  j

Laplace transforms of a few commonly encountered functions.

1- Exponential Function. Consider the exponential function

f(t) = 0 , for t < 0

f(t) = Ae-αt for t > = 0


where A and α are constants.
The laplace transform of this exponential function can be obtained as
following :-

 
A
 Ae dt  A  e  (  s ) t dt 
 t  t  st
[ Ae ] e
0 0
s 

2- Step Function.
Consider the step function

𝑓(𝑡) = 0 , 𝑓𝑜𝑟 𝑡 < 0


𝑓(𝑡) = 𝐴 , 𝑓𝑜𝑟 𝑡 ≥ 0

Where A is a constant

𝒔𝒕
𝑨
∴ 𝓵[𝑨] = 𝑨𝒆 =
𝑺
𝟎
3- Ramp Function.
Consider the Ramp function

𝑓(𝑡) = 0 , 𝑓𝑜𝑟 𝑡 < 0


𝑓(𝑡) = 𝐴𝑡 , 𝑓𝑜𝑟 𝑡 ≥ 0

Where A is a constant
𝒔𝒕
𝑨
∴ 𝓵[𝑨] = 𝑨𝒆 =
𝑺𝟐
𝟎

4- Sinusoidal Function.
The Laplace transform of the sinusoidal function is :

𝑓(𝑡) = 0 , 𝑓𝑜𝑟 𝑡 < 0


𝑓(𝑡) = 𝐴𝑠𝑖𝑛(𝜔𝑡) , 𝑓𝑜𝑟 𝑡 ≥ 0

Where A and 𝝎 are constants.

𝑨𝝎
∴ 𝓵[𝑨𝒔𝒊𝒏(𝝎𝒕)] =
𝑺𝟐 + 𝝎𝟐
Similarly, the Laplace transform of

𝑨𝒄𝒐𝒔(𝝎𝒕)

𝑨𝒔
∴ 𝓵[𝑨𝒄𝒐𝒔(𝝎𝒕)] =
𝑺𝟐 + 𝝎𝟐
 Translated Function.
Let use obtain

.
Ex :- consider 𝑓(𝑡) = 𝑒−𝑡 and 𝑓 =𝑒

∴ ℓ[𝑓(𝑡)] = ℓ[𝑒 ] = 𝑒 .𝑒 𝑑𝑡
( )
𝑒 ( )
= 𝑒 𝑑𝑡 = 𝑒 𝑑𝑡 =
−(1 + 𝑠)

1 1
= 0− =
−(1 + 𝑠) 𝑠+1

𝑡 .
ℓ 𝑓 = 𝑓(𝑡). 𝑒 𝑑𝑡 = 𝑒 .𝑒 𝑑𝑡
5

( . )
𝑒 ( . )
= 𝑒 . 𝑑𝑡 =
−(0.2 + 𝑠)
1 1 1
= 0− = , 0.2 =
−(0.2 + 𝑠) 𝑠 + 0.2 5

1 5
∴= =
𝑠+1 5
5𝑠 + 1

 Laplace Transform Theorems.

1- Real Differential Theorem.


The Laplace transform of the derivative of a function 𝑓(𝑡)
is given by

𝑑
ℓ 𝑓(𝑡) = 𝑆 𝐹(𝑠) − 𝑓(0)
𝑑𝑡

Where 𝑓(0) is the initial value of 𝑓(𝑡)


- For the second derivative of 𝑓(𝑡)

𝑑
ℓ 𝑓(𝑡) = 𝑆 𝐹(𝑠) − 𝑆 𝑓(0) − 𝑓̇(0)
𝑑𝑡

Where 𝑓̇ (0) is the value of 𝑓(𝑡) evaluated at 𝑡 = 0

- For the 𝑛 derivative of 𝑓(𝑡) we obtain

𝑑
ℓ 𝑓(𝑡) = 𝑆 𝐹(𝑠) − 𝑆 𝑓(0) − 𝑆 𝑓̇ (0) − ⋯ . …
𝑑𝑡
−𝑆𝑓 (0) − 𝑓 (0)

Where 𝑓(0), 𝑓̇ (0), … … … … … … . . 𝑓 (0) represent the value of


𝑓(𝑡), … … … … … . , 𝑓(𝑡) respectively evaluated at 𝑡 = 0

2- Final Value Theorem.


The final value theorem may be stated as follows if 𝑓(𝑡)
and 𝑓(𝑡) are Laplace transformable, If 𝐹(𝑆) is the laplace
transform of 𝑓(𝑡), and if 𝑙𝑖𝑚 𝑓(𝑡) exists then

𝐹(∞) = 𝑙𝑖𝑚 𝑓(𝑡) = 𝑙𝑖𝑚 𝑆 𝐹(𝑠)


→ →

3- Initial Value Theorem.


The initial value theorem may be stated as follows if 𝑓(𝑡)
And 𝑓(𝑡) are both Laplace transformable and if, 𝑙𝑖𝑚 𝑆 𝐹(𝑠) exists

than
𝑓(0) = 𝑙𝑖𝑚 𝑆 𝐹(𝑠)

4- Real Integration Theorem.

𝐹(𝑠) 𝑓 (0)
ℓ 𝑓(𝑡). 𝑑𝑡 = +
𝑆 𝑆

Where 𝐹(𝑠) = ℓ[𝑓(𝑡)] and 𝑓 (0) = ∫ 𝑓(𝑡). 𝑑𝑡 evaluated at 𝑡 = 0.

5- Complex – Differentiation Theorem.


If 𝑓(𝑡) is Laplace transformable, then, except at Poles of 𝐹(𝑠)

𝑑
ℓ[𝑡 𝑓(𝑡)] = − 𝐹(𝑠)
𝑑𝑠
where 𝐹(𝑠) = ℓ[ 𝑓(𝑡)]

𝑑
ℓ[𝑡 𝑓(𝑡)] = 𝐹(𝑠)
𝑑𝑠

In general

ℓ[𝑡 𝑓(𝑡)] = (−1) 𝐹(𝑠) , n = 1 , 2 , 3 , …………….

 Partial – Fraction Expansion Method For finding


Inverse Laplace Transforms.

𝐵(𝑠)
𝐹(𝑠) =
𝐴(𝑠)

Where 𝐴(𝑠) and 𝐵(𝑠) are polynomials in S, if 𝐹(𝑠) is broken up into


components

𝐹(𝑠) = 𝐹 (𝑠) + 𝐹 (𝑠) + ⋯ … … … … + 𝐹 (𝑠)

And if the inverse Laplace transform of 𝐹 (𝑠), 𝐹 (𝑠), … … … ..

Then
ℓ [𝐹(𝑠)] = ℓ [𝐹 (𝑠)] + ℓ [𝐹 (𝑠)] + ⋯ … … . + ℓ [𝐹 (𝑠)]

= 𝑓 (𝑡) + 𝑓 (𝑡) + ⋯ … … … … … + 𝑓 (𝑡)


𝐵(𝑠) 𝑘 ( 𝑠 + 𝑧 )( 𝑠 + 𝑧 ) ( 𝑠 + 𝑧 ) … … … . ( 𝑠 + 𝑧 )
∴ 𝐹(𝑠) = =
𝐴(𝑠) ( 𝑠 + 𝑃 ) ( 𝑠 + 𝑃 ) ( 𝑠 + 𝑃 )………….( 𝑠 + 𝑃 )

For 𝑚 < 𝑛

𝐵(𝑠) 𝑎 𝑎 𝑎
∴ 𝐹(𝑠) = = + + ⋯…………..+
𝐴(𝑠) 𝑠 + 𝑃 𝑠+ 𝑃 𝑠+ 𝑃

∴ 𝑓(𝑡) = ℓ [𝐹(𝑠)] = 𝑎 𝑒 + 𝑎 𝑒 + ⋯……….+ 𝑎 𝑒

You might also like